2014
DOI: 10.1002/j.0022-0337.2014.78.11.tb05827.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Case‐Based and Lecture‐Based Learning in Dental Education Using the SOLO Taxonomy

Abstract: The aim of this study was to compare the impact of case-based learning (CBL) and lecture-based learning (LBL) on fourth-year dental students' clinical decision making by using the Structure of Observed Learning Outcome (SOLO) taxonomy. Participants in the study were fourth-year dental students (n=55) in academic year 2012-13 taught in a large-group LBL context and fourth-year dental students (n=54) in academic year 2013-14 taught with the CBL methodology; both took place in the oral diseases course at Yeditepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 15 publications
1
27
0
3
Order By: Relevance
“…Another pathology article from Africa, describing a course in laboratory medicine for mixed graduate medical education (residents) and CME for clinicians, defines CBL: “Case-based learning is structured so that trainees explore clinically relevant topics using open-ended questions with well-defined goals.” 7 The exploring that students or trainees do factors into other definitions. In a dental education article originating in Turkey, the authors remark: “The advantages of the case-based method are promotion of self-directed learning, clinical reasoning, clinical problem solving, and decision making by providing repeated experiences in class and by enabling students to focus on the complexity of clinical care.” 8 Another definition of CBL was offered in a physiology education paper regarding teaching undergraduate medical students in India: “What is CBL? By discussing a clinical case related to the topic taught, students evaluated their own understanding of the concept using a high order of cognition.…”
Section: Discussion and Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Another pathology article from Africa, describing a course in laboratory medicine for mixed graduate medical education (residents) and CME for clinicians, defines CBL: “Case-based learning is structured so that trainees explore clinically relevant topics using open-ended questions with well-defined goals.” 7 The exploring that students or trainees do factors into other definitions. In a dental education article originating in Turkey, the authors remark: “The advantages of the case-based method are promotion of self-directed learning, clinical reasoning, clinical problem solving, and decision making by providing repeated experiences in class and by enabling students to focus on the complexity of clinical care.” 8 Another definition of CBL was offered in a physiology education paper regarding teaching undergraduate medical students in India: “What is CBL? By discussing a clinical case related to the topic taught, students evaluated their own understanding of the concept using a high order of cognition.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…Another attempt to measure deeper learning was reported from a dental school in Turkey. 8 The authors compared a CBL course with an older LBL course from the previous year by using “SOLO” taxonomy, developed by Biggs and Collis. 73 SOLO taxonomy rates the learning outcomes from prestructural through extended abstract.…”
Section: Discussion and Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…SOLO taxonomy measures learning from prestructural (de ine, identify) through extended abstract (evaluate, generalize, predict, create, hypothesize, re lect). Students who attended the case-based discussions had signi icantly higher scores in the higher mental order tasks of the SOLO compared to students only attending traditional lectures [6]. This study demonstrated advanced critical thinking skills in the group that attended case-based discussions.…”
Section: Introductionmentioning
confidence: 58%
“…They found that physicians had the lowest scores in reaching higher level of reflective thinking. Ilguy et al found significant benefit in higher level of learning using CBL program 17.…”
mentioning
confidence: 99%